Odpowiedzi

Najlepsza Odpowiedź!
2010-01-23T20:58:37+01:00
Układam równania:
b - a = c - b
a + b + c = 33
/ b + 3/: a = /c + 3/ : /b + 3/
==============================
2xb = a + c
a + c = 33 - b
/b + 3/^2 = ax/c + 3/
=========================
2 x b = 33 - b b = 11
a + c = 2 x 11 = 22
a = 22 - c
==================
/ 11 + 3/^2 = /22 - c/ x / c + 13/
196 = 22xc + 22x13 - c^2 - 13xc
c^2 - 9xc - 90 = 0
======================
delta = /-9/^2 - 4x1x/-90/= 441
pierwiastek z delty = "+"-"21
=========================
c1 = /-/-9/ - 21/2x1 = -6
c2 = /-/-9/ + 21/2x1 = 15
=========================
a1 = 22 - c1 = 28
a2 = 22- c2 = 7
===================
I rozwiązanie : a = 28, b = 11, c = -6 / r = - 17/
II rozwiązanie : a = 7 , b = 11, c = 15 / r = 4/

ateb
1 5 1